Values, Authenticity, and Responsible Leadership - Freeman, R. Edward (Journal of business ethics, 2011)
The recent financial crisis has prompted questioning of our basic ideas about capitalism and the role of business in society. As scholars are calling for “responsible leadership” to become more of the norm, organizations are being pushed to enact new values, such as “responsibility” and “sustainability,” and pay more attention to the effects of their actions on their stakeholders. The purpose of this study is to open up a line of research in business ethics on the concept of “authenticity” as it can be applied in modern organizational life and more specifically to think through some of the foundational questions about the logic of values. We shall argue that the idea of simply “acting on one’s values” or “being true to oneself” is at best a starting point for thinking about authenticity. We develop the idea of the poetic self as a project of seeking to live authentically. We see being authentic as an ongoing process of conversation that not only starts with perceived values but also involves one’s history, relationships with others, and aspirations. Authenticity entails acting on these values for individuals and organizations and thus also becomes a necessary starting point for ethics. After all, if there is no motivation to justify one’s actions either to oneself or to others, then as Sartre has suggested, morality simply does not come into play. We argue that the idea of responsible leadership can be enriched with this more nuanced idea of the self and authenticity.